The megalithic cist at Blære - Fabech, Charlotte; Crabb, Peter (Kuml, 1986)
The megalithic cist at Blære In the summer of 1982, a complete investigation of a Neolithic megalithic cist was carried out at Blære, Himmerland (1), Due to favourable conditions of preservation, afforded by thick layers of drift sand, it was possible to distinguish at least 10 burials in the cist, extending from the beginning to the end of the Late Neolithic (2). The secondary barrow The cist was found under an almost intact secondary barrow with stone capping and kerb (Fig. 1). The barrow (Fig. 2) covered an urn grave, A6, from the end of the Bronze Age, and centrally at the top a cremation grave, A1. The latter grave contained a rimsherd and a ring-headed pin of iron (Fig. 3a). Just outside the foot of the barrow, three more cremation graves were exposed, A2, A3 and A4, all containing pottery. The cremation grave A4 also contained an iron pin with discoid head (Fig. 3b). Both the pins mentioned can be dated to the first part of the Pre-Roman Iron Age (3); the same applies to the pottery. This date accords with that of the grave farm itself, which was common in central Jutland in the Late Bronze Age and Early Iron Age ( 4). The cist The barrow containing the cist was constructed of turf. The cist was in the centre of the mound and was, as is common in northern Jutland, oriented NNE-SSW, with the entrance to the south (5). The cist consists of a passage and a chamber (Fig. 4). The inside measurements of the chamber are: length 3.90 m, width 2.25 m and height 1.20 m. Each side is constructed of five relatively flat stones, 30-40 cm thick. Six stones have cleavage surfaces on the inside and the remaining four on both sides (6). The end wall consists of two c. 30 c thick stones with one cleavage surface. The inside dimensions of the passage are: length 2.25 m, width 0,60 m and height 0,70 m. It consists on the west side of a c. 60 cm wide and 2 m long stone with cleavage faces on both sides. The east side is formed by three c. 30 wide and 50 cm long stones with two cleavage faces, and furthest south, a small fieldstone. The chamber is capped with three stones, respectively measuring 2.6X 1.6 m, 2.3X 1.5 m and 2.0X 1.1 m, 30-60 cm thick, and a smaller stone over the southwestern corner of the chamber. They all have a cloven under-surface - and the central capstone a cloven top. The passage is covered by two small stone stabs. The cist was set about 1 m into the subsoil. The profiles show that the stones were placed in a narrow trench and that the spoil had been cast to both sides of the hole (Fig. 5). The passage was marked with two thresholds, each consisting of a single thin stone slab. The orthostats of the chamber all incline slightly inwards and are wedged upright with smaller stones (Fig. 6a). The intervals between capstones and orthostats were further filled with smallstone packing (fig. 6b). Further support for the cist was provided by a stone packing placed around the foot of the chamber (fig. 6c), and its entrance was dosed with fieldstones and small stone stabs (fig. 6d). The cist was also covered by flags (fig. 6e). Over this the barrow was placed - according to the profile Fig. 5 it seems to have covered the cist entirely. The Blære cist is allied in form and construction to the Gravlev, Torderup, Bøstrup and Blegødal cists and must like these have been erected either in late bottom grave or upper grave times. Content and interpretation of the cist A reconstruction of the course of events in and around the Blære cist is, as always when graves which have been utilized for repeated burial are involved, attended by a certain amount of uncertainty. But among other things the intrusion of sand, and the fact that the cist had stood undisturbed since the last burial, allowed at least 10 burials to be distinguished among the many finds in the cist itself. The first burial must have been carried out immediately after the cist was constructed. The dating of the cleared material, amber beads (36), pottery (37) and a D-arrowhead (38) (Fig. 17 and 18), and the construction of the cist, revealed that this must have occurred in late bottom grave or upper grave times. Whether more than one burial occurred within the Single Grave culture cannot be decided. Early in the Late Neolithic, the cist again came into use. This burial, "grave 7", could be observed as a grey-black patch of soil with remains of charcoal. The contents - a pot, an amber button and three amber beads (Fig. 14, 15 and 16) - are dated to Late Neolithic A (31, 33, 35). The amber button, which has a V-shaped perforation, shows an influence from the Bell Beaker complex (32, 34). The fact that the amber beads lay together and the pot stood undamaged in this layer can indicate that there was a wooden coffin, set slightly into the subsoil. Judging from the contents of the very disturbed "grave layer 6", including four type I flint daggers, nine flat-flaked arrowheads, a sherd from a Bell Beaker decorated vessel (Fig. 12 and 13) and a cremation grave, at least four more persons were buried in the cist in Late Neolithic A (27, 28, 29, 30). The objects lay, as mentioned earlier, scattered among many fieldstones. These stones are too large to have entered the cist by accident, but whether they formed a small cist, a paving, or were brought in as supports for a wooden coffin could not be decided. Before the coffin for the next burial, "grave 3", was constructed, the earlier burials were levelled out without destroying the cremation grave, which lay right out at the eastern edge of the chamber. After this, fieldstones were placed so as to support the coffin, which judging by the shape of the preserved traces must have been a large planked cist (Fig. 7). At the bottom of this coffin was a cowhide (21) on which the corpse must have been laid. The grave goods - a flint sickle, three amber beads (Fig. 11a and b) and a wooden dish - could not date the grave precisely. The flat-flaked flint sickle indicates, however, that burial did not occur before the last part of the Neolithic (22, 23, 24, 25). The plank coffin thereafter remained undisturbed for so long that intrusive sand was deposited in a 15-20 cm thick layer over and beside the coffin, before the next burial was carried out. The custom of interring the dead in a plank coffin inside the stone cist itself is also known from the Kobberup cist at Skive (26). It is dated to the Single Grave culture. The cist was used once more. This time the body was placed at the north end of the cist in "grave 2" and was, besides a small locally produced pot, accompanied by such rare metal objects as a little disc-headed pin of copper (10) with a rolled eye and a spiral ring (Fig. 9a and c). The provenance of both objects may be south Germany. On the pin were found remains of cow-hair (20), which suggest that this body, too, was placed on a cowhide. The dating of the disc-headed pin to Reinecke A1 indicates that this burial occurred in Late Neolithic C (11, 12, 13, 14, 15, 16), a date which agrees with the dating of the spiral ring (17, 18) and the pot (19). At the northwestern corner of the chamber lay, in the same deposit, but 10 cm deeper, a flake axe and a symmetrical flat-flaked flint sickle side by side (Fig. 10). It could not be ascertained whether these two objects belonged to "grave 2". In the southwestern corner of the chamber, the coffin traces from "grave 3" and the yellow drift sand around them showed signs of disturbance. The cause was two burials placed partly in the cist passage and in the front part of the chamber (Fig. 7). "Grave 1" was placed at the south end of the chamber, its only traces being a small setting of stones and perhaps a re-utilized amber disc (Fig. 8). The amber disc could, if it belongs with the stone setting, not give any secure dating of the burial (8, 8), but as the grave was placed well up in the chamber above that with the disc-headed pin, we must assume that it derives from late Late Neolithic C or the Early Bronze Age. There are no signs that the cist was been disturbed after the construction of this grave. The chamber was then blocked with stones and seems not to have been opened since. At the transition between the Bronze Age and the Pre-Roman Iron Age, the barrow with the megalithic cist was again utilized as a burial mound. After this, it was covered by several layers of drift sand. It is uncertain when this occurred. Judging from other investigations, from which we learn that Himmerland was subjected to considerable sand drift in the centuries before the birth of Christ, it is likely that the sanding up of the mound occurred in the last part of the Roman Iron Age. From the profile (Fig. 7) it is apparent that the layers of drift sand were not formed on a single occasion: between the layers of wind-blown sand, heath profiles and growth layers can be observed, attesting that the barrow managed to become stabilized between sand drifts (39). A Change in burial-custom? The megalithic cist from Blære was constructed and used at the end of the Single Grave Culture, but its principal use as sarcophagus occurred in the Late Neolithic. It is therefore considered whether the burial custom as it is manifested in the cist remained unaltered throughout the Late Neolithic. The late cist burials with flint sickle, flake axe and metal ornaments displayed the introduction of new artefact types among the burial goods. But the most obvious change is perhaps that flint daggers do not occur in the late graves. Despite the cist having been used for burial throughout the Late Neolithic, it contained only type I daggers. According to T. Madsen's investigation of the chronological and regional circumstances attending the different dagger types (40), we ought, if the flint dagger was used just as often as a burial gift in Late Neolithic B/C as in Late Neolithic A, have found daggers of types III, IV and V in the Blære cist. We should therefore examine how the different types of daggers are distributed among the find categories hoard, grave and casual find, in order to discover whether there is any difference in the circumstances under which they were found. From Fig. 19 it is apparent that 50 % of the type I and II daggers have been found in graves, but this is the case only with 21-39% of types III-VI. The same picture can be observed among the daggers found in hoards, 14-18% of types I-II having been found in hoards as against 1-7 % of types III-VI. Casually found daggers show the opposite picture: only 34 % of type I-II daggers derive from casual finds, while 59-72 % of types III-VI do so. This marked discrepancy in the representation of the various dagger types in different find categories cannot be rooted in source-critical circumstances alone. There is nothing to indicate that especially many grave and hoard finds in a particular geographical area, with type III-VI daggers, should have been destroyed by, for example, construction and agricultural work, while graves and hoards with types I-II in the same area remained undamaged, when we know that the same grave and hoard forms occur throughout the Late Neolithic. The above shows that the absence of type III, IV and V daggers in the Blære cist is not peculiar to that, but agrees with a general fall-off in the occurrence of these dagger types in grave and hoard finds. Such a change in the use of the flint dagger accords with the fact that other artefact types, such as flint sickles and weapons and ornaments of metal, start to appear as grave goods. Altogether, this gives the impression that the grave goods at the end of the Late Neolithic were more differentiated than earlier - perhaps reflecting a more complex society (41, 42). The graves in the Blære cist thus gives an impression of a society which throughout the Late Neolithic was open to outside influences - to begin with in the form of Bell Beaker impulses, later through, for example, metal objects - a society which had sufficient influence and resources to obtain the current prestige symbols, but which due to the nature of these contacts was altered to a more hierarchic one (43, 44). Charlotte Fabech